Attitudes, practices, and obstacles towards influenza vaccination for international travelers among travel health advisors in Germany: A questionnaire-based survey. Issue 45 (January 2022) - Brehm, Thomas Theo; Jordan, Sabine; Addo, Marylyn M.; Ramharter, Michael; Kreuels, Benno
Abstract: Background: Influenza is the most frequent vaccine-preventable infection in travelers, and both national and international guidelines recommend considering seasonal influenza vaccination (SIV) not only for those with risk factors for complications but for all travelers. However, vaccination coverage may be hampered by a lack of awareness among travelers and health care providers and limited vaccine availability outside the local influenza season. Methods: We identified travel health advisors in databases of German medical professional societies and invited them to complete an online questionnaire between April and May 2021. Results: Among 1085 travel health advisors contacted by email, 253 (23.3%) completed the online questionnaire. Most of them recommend SIV for travelers older than 60 years or those with comorbidities regardless of the travel destination or the influenza season in Germany. However, only very few respondents stated that they had regular access to SIV in June (n = 16, 6.5%), July (n = 10, 4.0%), and August (n = 17, 6.9%), respectively. While most participants (n = 197, 79.4%) stated that they would vaccinate more travelers if they had SIV regularly available outside the German influenza season, only eleven respondents (4.4%) have previously ordered SIV produced for the southern hemisphere, which was attributed mainly to logistic barriers. Conclusions: Travel health advisors in Germany recommend SIV for a considerable proportion of travelers. While most of them see a necessity to vaccinate throughout the year, availability of SIV outside the German season is very limited. Current organizational barriers must be overcome to increase vaccination coverage among international travelers.